2013
DOI: 10.1111/raq.12034
|View full text |Cite
|
Sign up to set email alerts
|

Fantastically plastic: fish larvae equipped for a new world

Abstract: Teleost fish are more diverse than any other vertebrate group, and yet only a limited number of species are fished and farmed globally. Efforts to expand the quantity and diversity of fish produced are hampered by the extreme diversity of ontogenetic responses of fish, especially during larval development. This review looks at advances in molecular phylogeny, endocrine and nutrient influences and long-term studies of the phenotypes of commercially important fish to put the sources and consequences of this plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 372 publications
0
74
0
4
Order By: Relevance
“…The trout alevins were fed from first-feeding (at mouth opening) diets with low or high carbohydrate/protein ratio and then challenged to eat a high-carbohydrate diet at the later juvenile stage. Compared with mammals, trout alevins (larvae) constitute a powerful and unique model with which to try to modify metabolism because of the very high plasticity (Pittman et al, 2013, Mennigen et al, 2013 and the direct acceptability of exogenous solid feed at this developmental stage. Indeed, drastic changes in metabolic gene expression occur in first-feeding rainbow trout, during the transition from endogenous (yolk-sac) to exogenous feeding, as illustrated for some genes involved in carbohydrate utilisation (Geurden et al, 2007) and for the expression of miRNAs that may contribute to the ontogenetic metabolic changes (Mennigen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The trout alevins were fed from first-feeding (at mouth opening) diets with low or high carbohydrate/protein ratio and then challenged to eat a high-carbohydrate diet at the later juvenile stage. Compared with mammals, trout alevins (larvae) constitute a powerful and unique model with which to try to modify metabolism because of the very high plasticity (Pittman et al, 2013, Mennigen et al, 2013 and the direct acceptability of exogenous solid feed at this developmental stage. Indeed, drastic changes in metabolic gene expression occur in first-feeding rainbow trout, during the transition from endogenous (yolk-sac) to exogenous feeding, as illustrated for some genes involved in carbohydrate utilisation (Geurden et al, 2007) and for the expression of miRNAs that may contribute to the ontogenetic metabolic changes (Mennigen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Different zootechnical conditions can affect the adequate development, growth and survival of larvae and production of juveniles of quality. The general development of marine fish eggs and larvae follows a similar pattern, but apparently important speciesspecific differences exist with regard to different biotic and abiotic factors (feeding regimes and behaviours, temperature and climate ranges and others), and with regard to a particular sequential timing of development and functionality of the main organ systems during the larval life (Govoni et al 1986, Dinis et al 1999, Pittman et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the use of histological and histochemical approaches during larval fish ontogeny (Sarasquete 1993a,b, 1995, Segner et al 1994, Ortiz-Delgado et al 2003 may aid the identification of growth patterns and larval critical periods. Several biochemical, physiological and cellular biomarkers can also provide information for the monitoring and optimization of rearing technologies, optimal feeding protocols, nutritional requirements and feeding behaviours (Govoni et al 1986, Zambonino-Infante et al 2008, Hamre et al 2013, Pittman et al 2013 in order to achieve the best improvements for increasing the efficiency in a sustainable fish production (i.e. optimal growth and survival and reduced costs).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, some authors have reported that an improper or abrupt weaning schedule might delay the development of the stomach (Hamza et al, 2007;Liu et al, 2012). In stinging catfish, regardless of the weaning schedule tested, no differences in the level of cellular organization and development were observed among treatments at the end of the study, which indicated high plasticity of this catfish larvae to different nutritional conditions once their digestive system was completely developed and larvae were adapted to the microdiet (Pittman et al, 2013;Rønnestad et al, 2013). Similar to the present study, in shi drum Umbrina cirrosa, Papadakis et al, (2009) also observed lower growth in early weaned larvae without any influence on the timing of the appearance of the various components of the digestive system.…”
Section: Resultsmentioning
confidence: 84%